City planning related to the completion of the new high speed line in Rennes, Brittany - Romaric Nègre; Guy Baudelle (Belgeo)
Over the last decades, the metropolitan area of Rennes (Western France) has experienced a sharp demographic and economic dynamism compared with other similar French urban areas. The new high-speed line between Le Mans and Rennes (hereafter BPL HSL) to be opened in 2017 is carrying major expectations from local public actors. In this paper, we examine urban projects associated with the high-speed line in Rennes as tangible spatial expressions of a global prospective vision for Rennes post-BPL HSL. Analyzing the main factors explaining the vibrancy of the metropolitan area, we focus on the territorial positioning of Rennes and its attempts to capture the “HSL opportunity” and accelerate the current pace of socioeconomic dynamism. However, such an urban growth strategy introduces a sharp competition in the new office market between central projects and peripheral investments.